Evaluating the Response of Some Maize (Zea mays L.) Genotypes to Organic and Inorganic Fertilizers Under Irrigated Conditions (Damascus University Journal of agriculture sciences, 2022)
A field experiment was conducted in first May Research Station affiliated to the General Commission for Scientific Agricultural Research (GCSAR) during the growing season 2020, to evaluate the effect of seven organic and chemical fertilizers treatments on the growth and productivity of maize genotypes (Salamia-1, Salamia-2, Ghouta-82 and SH). The experiment was laid out according to Randomized Complete Block Design in split plot arrangement with three replications.Results clearly indicated the existence of genetic variability in the response of the studied maize genotypes to fertilization treatments. The genotype SH at the treatment of 50 % of fertilizers through poultry manure + 50 % through chemical fertilizers recorded significantly the highest mean values of leaf area index, plant dry weight, cob length, number of grains per cob, and grain yield (3.01, 350 g, 16.34 cm, 626 grains.cob-1, 9560 kg.ha-1 respectively) and was closely followed by the genotype Ghouta-82 at the same fertilization treatment ( 2.71, 346.28 g, 15.67 cm, 570 grains.cob-1, 8675 kg.ha-1 respectively). Therefore, it can be recommended to grow the genotype SH or Ghouta-82  and adding 50 % of fertilizers through poultry manure + 50 % through chemical fertilizers to get the highest maize grain yield in the targeted area.
Keywords: Chemical fertilizers; Organic manure, Grain yield; Maize